Proteogenomics and its applications in biology and precision medicine - Van Chi, Phan; Thi Bich Thao, Le (Vietnam Journal of Biotechnology, 2021)
In this review, we briefly discuss proteogenomics, the integration of proteomics with genomics and transcriptomics, whereby the underlying technologies are next-generation sequencing (NGS) and mass spectrometry (MS) with processing the resulting data, an emerging field that promises to accelerate fundamental research related to transcription and translation, as well as its applicability. By combining genomic and proteomic information, scientists are achieving new results due to a more complete and unified understanding of complex molecular biological processes. Part of this review introduces some of the results of using proteogenomics in solving problems such as annotation, gene/genome re-annotation, including editing of open reading frames (ORFs), or improving a process to detect new genes in a number of different organisms, including humans. In particular, the paper also discusses the potential of proteogenomics through research achievements on human genome/proteome in precision medicine, especially in projects on phylogenetic and diagnostic research. and cancer treatment. The challenges and future of proteogenomics are also discussed and documented.